Specialists' Perception of the Harmful Consequences of Child-Abuse: A Phenomenological Study - Mousa Choupani; Faezeh Atefi (Kerman University of Medical Sciences, 2021)
Introduction: Child-abuse is one of the most common socio-psychological problems, and can contribute to the development of a set of intrapersonal, interpersonal, and peripheral harms in child and adolescent victims. This study aims at identifying the harmful consequences and harms of childabuse (child maltreatment) in child and adolescent victims from the perspective of specialists (counselors, psychologists, and social workers). Methods: This study was carried out using a qualitative and interpretive phenomenological approach. The research population included all specialists in the field of psychological and social health (counselors, psychologists, and social workers) in Isfahan and Tabriz Universities in 2018, who were experienced in research and treatment in child abuse. The participants were 9 specialists who were selected using purposive sampling. The data were collected through interviews with the participants. All the interviews were recorded and then transcribed line by line. The data extracted from the interviews were analyzed using the interpretive analysis approach proposed by Diekelmann, Allen, and Tanner. Results: The analysis of the data extracted from the interviews revealed five main themes (psychological, behavioral, interpersonal, family, and social harms) and 31 subthemes related to child-abuse harms and consequences from the perspective of the specialists. Conclusion: The insights from this study can be used to develop educational, preventive, and therapeutic programs aimed at reducing child abuse and its harmful effects.